Reformulasi Kedudukan MPR Dalam Sistem Ketatanegaraan Indonesia Pasca-Amandemen UUD 1945 Perspektif Hukum Tata Negara Islam Kontemporer - Diki Yumansyah; Bachder Syarif Arkiang; M. Jasuli Ramadhan; Muhammad Al Farid; Muhtar (Maqasid: Jurnal Studi Hukum Islam, 2025)
This research examines the reformulation of the status of the People’s Consultative Assembly (MPR) within Indonesia’s constitutional system after the amendment of the 1945 Constitution, using a convergent approach between positive constitutional law and contemporary Islamic constitutional thought. Following the amendments, the MPR was transformed from the highest state institution into a high state organ equal to others, thereby losing part of its strategic function. By employing the principles of shūrā, ahl al-ḥall wa al-ʿaqd, and maqāṣid al-sharīʿah, this study offers an alternative perspective to strengthen the role of the MPR as a moral-constitutional institution. The findings reveal that integrating Islamic ethical values with Pancasila has the potential to enrich the substantive dimension of Indonesian democracy. The reformulation emphasizes the importance of reinforcing ideological evaluative functions, establishing a national deliberative forum, and enhancing the ethical capacity of MPR members as strategic efforts toward more dignified and just governance.